Digital economy: Trends, challenges, and development prospects - Oksana Khilukha (Economic Forum, 2024)
The relevance of the topic is driven by the rapid development of information technologies, which are transforming business models, consumer habits, and methods of conducting economic activities. In a world, where digital technologies are becoming the foundation for innovation and competitiveness, understanding the processes taking place in the digital economy is critically important. The purpose of the article was to systematise the main trends in the development of the digital economy, identify the challenges faced by governments, businesses, and society as a whole, and assess the prospects for digital transformation in various sectors of the economy. To achieve this goal, it was apply a comprehensive analytical method, which included a review of scientific articles, analysis of statistical data, as well as a study of digitalisation practices in different countries. The findings confirmed that the digital economy has significant potential to stimulate economic growth, increase productivity, and create new jobs. However, despite the positive outlook, the article also identified serious challenges, such as inequality in access to digital technologies, cybersecurity issues, and the need to adapt legislation to new market conditions. Additionally, it emphasised that not all countries have equal opportunities to leverage digital technologies, which may lead to increased inequality between them. The article also proposed approaches to forming partnerships between government institutions, businesses, and educational establishments to ensure the successful integration of digital technologies into all areas of life. Key investment areas have been identified, including infrastructure development, raising the level of digital education, and supporting innovation and startups. The practical value of the study lies in the development of recommendations for shaping effective government policies and strategies that can promote the development of the digital economy
Keywords: 330; digital transformation; digital technologies; Internet; social networks; cellular mobile connections